. The bioclimatic com fort standard for the city of Amaraand its outskirts - Sabah Baji Diwan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The variation in the climatic conditions of a particular region has a direct effect on the extent of a person’s sense of bioclimatic comfort, as this comfort varies according to the variation of these conditions. The research was concerned with studying the standard of bioclimatic comfort for the city of Amara during the hot season influenced by several factors. The building material and the site, the first model with a concrete roof and the second model of perforated bricks, are located within the city center in (Al-Yarmouk district) and the second is at the edges of the center within (the university district), and it was found that there is a discrepancy in the extent to which the two models approach the rest area, where the lowest degree was recorded Heat of the two models on the outskirts of the city center, which was reflected in the influence hours of heat transfer through the walls and ceilings of the two areas.